Prevalence and determinants of gestational diabetes mellitus in Africa based on the updated international diagnostic criteria: a systematic review and meta-analysis - Muche, Achenef Asmamaw (Arch Public Health, 2019)
BACKGROUND: Gestational diabetes mellitus (GDM) is a major public health problem and threat to maternal and child health in Africa. No prior review has been conducted in Africa using the updated GDM diagnostic criteria. Therefore, this review aimed to estimate the pooled prevalence and determinants of GDM in Africa by using current international diagnostic criteria. METHODS: A systematic review and meta-analysis was conducted by comprehensive search of the published studies in Africa. Electronic databases (PubMed, Scopus, Cochrane Library, EMBASE, Google Scholar, CINAHL, Web of Science, Science direct and African Journals Online) were searched using relevant search terms. Data were extracted on an excel sheet and Stata/ SE 14.0 software was used to perform the meta-analysis. Heterogeneity of included studies were assessed using I(2) and Q test statistics. I(2) > 50% and Q test with its respective p-value < 0.05 were suggestive for the presence of a significant heterogeneity. Publication bias was assessed using the Egger‘s regression test and funnel plot. Subgroup and sensitivity analyses were done. A random effects model was used to estimate the pooled prevalence of GDM and odds ratio (OR) with 95% confidence interval (CI). RESULT: A total of 23 studies were included in the final analysis. The pooled prevalence of GDM in Africa was 13.61% (95% CI: 10.99, 16.23; I(2) = 96.1%), and 14.28% (95% CI, 11.39, 17.16; I(2) = 96.4%) in the sub-Saharan African region. The prevalence was highest in Central Africa 20.4% (95% CI, 1.55, 38.54), and lowest in Northern Africa 7.57% (95% CI, 5.89, 9.25) sub- regions. Overweight and obesity, macrosomia, family history of diabetes, history of stillbirth, history of abortion, chronic hypertension and history of previous GDM had positively associated with GDM. CONCLUSIONS: The prevalence of GDM is high in Africa. Being overweighed and/or obese, ever had macrocosmic baby, family history of diabetes, history of stillbirth, history of abortion or miscarriage, chronic hypertension and history of previous GDM were factors associated with GDM. Preventing overweighed and obese, giving due attention to women having high-risk cases for GDM in pregnancy are strongly recommended to mitigate the burden. SYSTEMATIC REVIEW REGISTRATION: PROSPERO (2018:CRD42018116843). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13690-019-0362-0) contains supplementary material, which is available to authorized users.